Türkiye’de bölücü kürtçü hareketler (1961-1980) - Akkurt, Mutlu (My University, 2019)
Şark Meselesi olarak Osmanlı Devletinin, Kürt Sorunu, Kürtçülük, Terör Sorunu gibi isimlerle Türkiye Cumhuriyetinin önüne engel olarak sunulan bu mesele, yıllardır çözülmeyi beklemektedir.

Orient issue as the Ottoman Empire, it remains to be solved for many years about Kurdish problem, Kurdish nationalism, this issue is presented as an obstacle in front of the name as the Republic of Turkey Terror Problem.
Keywords: Bölücü Terör; Ethnic relations; Ethnic Terror; Etnik ilişkiler; Etnik Terör; Kurdism; Kurds; Kürt Sorunu; Kürtçülük; Kürtler; PKK; PKK Kurdish Problem; Politics and government; Politika ve idare; Separatist Terror; Terör Sorunu; Terror Problem; Turkey; Turkey, Eastern; Türkiye; Türkiye, Doğu